The ephemerae of digital literature. - Bootz, Philippe (Neohelicon, 2021)
Digital literary productions often combine both the ephemeral dimensions of their screen-readable manifestation and the perennial dimension of their program. Their status thus lies between a totally ephemeral pole of performance and a totally perennial pole of reproducible publication. This "two-sided" status questions our conception of the work. The article begins with a pragmatic analysis of the forms of variability and transience present in print and digital literatures. It then examines how the most common conception of the work deals with these properties by proposing a formulation of this dominant viewpoint in the form of a "front-end dispositive." Recognizing a blind spot in thinking, he examines how these properties are addressed in models that are better suited to the digital, notably the procedural model. It concludes by proposing the concept of "reading machine," a technological system that aims to give access to the semiotic dimensions that develop outside screen reading, without suppressing the ephemeral.